2005
DOI: 10.1002/jid.1259
|View full text |Cite
|
Sign up to set email alerts
|

Aid and growth in Sub‐Saharan Africa: accounting for transmission mechanisms

Abstract: This paper is a contribution to the literature on aid and growth. Despite an extensive empirical literature in this area, existing studies have not addressed directly the mechanisms via which aid should affect growth. We identify investment as the most significant transmission mechanism, and also consider effects through financing imports and government consumption spending. With the use of residual generated regressors, we achieve a measure of the total effect of aid on growth, accounting for the effect via i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
108
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(131 citation statements)
references
References 22 publications
11
108
2
2
Order By: Relevance
“…The first studies claim that foreign capital inflow is necessary and sufficient for economic growth in lessdeveloped countries. They assert that there is a positive relationship between aid and economic growth because it not only augments domestic resources, but also supplements domestic savings, assists in closing the foreign exchange gap, creates access to modern technology and managerial skills, and allows easier access to foreign markets, ultimately leading to economic growth (Chenery & Strout, 1996;Islam, 1992;Dalgaard, Hansen & Tarp, 2004;Gupta & Islam, 1983;Burnside & Dollar, 2000;Hansen & Tarp, 2000;Morrissey, 2001;Gomanee et al, 2005). By the same token, Pallage and Robe (2001) noted that foreign aid is a major source of economic growth for developing countries, especially in Africa, where it averages 12.5 per cent of the gross domestic product and establishes by far the most important source of foreign capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first studies claim that foreign capital inflow is necessary and sufficient for economic growth in lessdeveloped countries. They assert that there is a positive relationship between aid and economic growth because it not only augments domestic resources, but also supplements domestic savings, assists in closing the foreign exchange gap, creates access to modern technology and managerial skills, and allows easier access to foreign markets, ultimately leading to economic growth (Chenery & Strout, 1996;Islam, 1992;Dalgaard, Hansen & Tarp, 2004;Gupta & Islam, 1983;Burnside & Dollar, 2000;Hansen & Tarp, 2000;Morrissey, 2001;Gomanee et al, 2005). By the same token, Pallage and Robe (2001) noted that foreign aid is a major source of economic growth for developing countries, especially in Africa, where it averages 12.5 per cent of the gross domestic product and establishes by far the most important source of foreign capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Robinson and Tarp, 2000, Beynon, 2001Morrissey, 2002). Gomanee et al (2002) analyse aid transmission mechanisms, channels through which aid can potentially contribute to growth. Aid can effect growth directly, but also through its impact on investment, imports, public sector fiscal aggregates and government policy.…”
Section: Towards a Consensus?mentioning
confidence: 99%
“…Notwithstanding, the positive sign on the inflation measure and government consumption spending contradicts the negative link found in cross-country growth regressions (e.g., Barro, 1996;Sala-i-Martin et al, 2004;Gomanee et al, 2005), although some studies have found favorable effects in the case of government consumption spending (Yasin, 2003).…”
Section: Does the Quality Of Foreign Aid Matter To Economic Growth?mentioning
confidence: 85%